1988
DOI: 10.1007/bf03010545
|View full text |Cite
|
Sign up to set email alerts
|

Priming with anticholinesterases — the effect of different priming doses of edrophonium

Abstract: The effect of different priming doses of edrophonium were studied in 77 patients divided into seven groups (n = 11 in each). Edrophonium ] .0 mg.kg -I was administered either dn a single bolus dose (Group I: controls) or in on initial dose of O.05, O. 1, O-15, 0,2, 0.25 We reported that divided administration of neostigmine or edrophonium hastens the recovery of atracurium-induccd neuromuscular blockade as compared to a single bolus administration of the antagonist, t,2 We also demonstrated that a one minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A priming dose of 0.2 mg.kg-' was reported to be the most effective in the range of 0.05-0.3 mg.kg-t. 4 Finally, the three-minute priming interval, when applied to 0.2 mg. kg -t followed by 0.8 mg. kg -~, was associated with the shortest reversal time among different combinations tested in another study. 3 The only apparent difference between this study and those of Naguib et al [2][3][4][5] is the inhalational agent used; enflurane was used in this study instead of halothane. Our choice was dictated by the popularity of the agent in clinical practice and in an attempt to "stress the system."…”
Section: Discussionmentioning
confidence: 77%
“…A priming dose of 0.2 mg.kg-' was reported to be the most effective in the range of 0.05-0.3 mg.kg-t. 4 Finally, the three-minute priming interval, when applied to 0.2 mg. kg -t followed by 0.8 mg. kg -~, was associated with the shortest reversal time among different combinations tested in another study. 3 The only apparent difference between this study and those of Naguib et al [2][3][4][5] is the inhalational agent used; enflurane was used in this study instead of halothane. Our choice was dictated by the popularity of the agent in clinical practice and in an attempt to "stress the system."…”
Section: Discussionmentioning
confidence: 77%
“…This acceleration of recovery was noted during antagonism of atracurium blockade as well. [4][5][6][7] found that divided administration anticholinesterases did not result in acceleration of recovery of atracurium blockade.t~'~2 Others administered repeated doses of neostigmine (70 p,g. kg-' each) in the presence of profound vecuronium neuromuscular blockade and concluded that repeated administration of neostigmine provided no evidence of hastened recovery, t3…”
Section: Discussionmentioning
confidence: 99%
“…3 We have demonstrated previously that a marked acceleration of recovery of atracurium neuromuscular blockade could be achieved with the administration of edrophonium in divided doses. [4][5][6][7][8] This study was designed to determine whether divided administration of different doses of edrophonium could alter the course of neuromuscular recovery from a pipecuronium neuromuscular blockade.…”
Section: Nous Avons Voulu Evaluer L' Effet De La Fragmentation De Dosmentioning
confidence: 99%